Improving Patient Families' Understanding of BPJS Health Service Procedures and Patient Rights through Participatory Health Education at Karo District Hospital - Linda Purwanti; Ade Aulia Siahaan; Arianus Zebua; Miftahul Jannah (Journal of Community Service and Empowerment, 2026)
The National Health Insurance (JKN) program administered by BPJS Kesehatan aims to provide comprehensive health protection for all Indonesian citizens; however, its implementation still faces low participant understanding of service procedures and patient rights, particularly among families of inpatients. This community service activity aimed to improve the knowledge of inpatients' families at Karo Regency General Hospital regarding the BPJS Kesehatan service flow and patient rights. The activity was conducted on 13 April 2026 in the hospital auditorium using a participatory health education approach comprising interactive lectures, question-and-answer sessions, and educational leaflets, involving 30 families of inpatients. Effectiveness was evaluated through pre-test and post-test using a validated 20-item questionnaire (r > 0.3; Cronbach's alpha = 0.82). Results showed a significant increase in knowledge, with the proportion of participants in the good category rising from 20.0% to 76.7%, and the mean score increasing from 47.8 ± 12.1 to 79.2 ± 9.4 (p < 0.001, Wilcoxon signed rank test). The largest gains occurred in the domains of service flow/referral system and inpatient administrative procedures (+50.0% each). These findings confirm that participatory health education effectively improves patient families' literacy regarding the JKN system and patient rights, and is recommended for routine, sustained implementation in hospitals